DAMPAK LIMBAH DOMESTIK TERHADAP KONDISI KUALITAS AIR DAN KERAGAMAN JENIS IKAN DI PERAIRAN RAWA TATAH BANGKAL KELURAHAN KELAYAN TIMUR KOTA BANJARMASIN - Elrifadah; Mukhlisah; Annisa Dwi Murdiani (Chlorophyl, 2025)
The waters of the Tatah Bangkal swamp have an important ecological and economic role, especially as a habitat for various fish species. However, the entry of domestic waste can cause changes in water quality and have an impact on the survival of aquatic biota. This study aims to determine the impact of domestic waste on water quality and the diversity of fish species in the waters of the Tatah Bangkal Swamp RT 34, Kelayan Timur Village, Banjarmasin City. The method used in this study is descriptive qualitative. Observations were carried out for 15 days with water quality parameters observed ex situ including Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and ammonia (NH3), while temperature, dissolved oxygen (DO), and pH were observed in situ. In addition, interviews with local people were conducted to determine changes in fish species in the waters. The results showed that the water temperature ranged from 27.2–27.6°C with a pH of 7.63–9.09. BOD values ​​range from 16.89–17.57 mg/L, COD 17.85–21.53 mg/L, DO 1.13–1.40 mg/L, and NH3 0.3–0.8 mg/L. Based on Class III water quality standards in PP No. 22 of 2021, several water quality parameters do not meet the standards, especially pH, BOD, and DO. Interviews with the community showed that since 2016 there has been a decline in fish catches, including the loss of local species such as papuyu fish (Anabas testudineus) and catfish (Oxyeleotris marmorata). This decline is thought to be caused by water pollution from domestic waste and the dominance of invasive species, such as catfish (Pterygoplichthys spp.)